2020
DOI: 10.1007/s11418-020-01466-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-directed activation of cryptic natural product pathways deciphers codes for biosynthesis and molecular function

Abstract: Natural products, which can be isolated from living organisms worldwide, have played a pivotal role in drug discovery since ancient times. However, it has become more challenging to identify a structurally novel molecule with promising biological activity for pharmaceutical development, mainly due to the limited methodologies for their acquisition. In this review, we summarize our recent studies that activate the biosynthetic potential of filamentous fungi by genetic engineering to harness the metabolic flow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…It has been confirmed that CC1G_04210 (cpf1) Siderophores are generally synthesized by two pathways: An NRPS-dependent pathway and an NRPS-independent pathway. It has been confirmed that CC1G_04210 (cpf1) encodes a siderophore synthetase and this NPRS cluster is responsible for the production of coprinoferrin, which is necessary for extracellular iron acquisition and is crucial for the growth and maturation of C. cinerea [46]. Homologous comparison and transcriptome analysis revealed that the NRPS cluster (cluster 6 in Figure S9) in S. rugosoannulata might be responsible for the production of coprinoferrin-related compounds.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It has been confirmed that CC1G_04210 (cpf1) Siderophores are generally synthesized by two pathways: An NRPS-dependent pathway and an NRPS-independent pathway. It has been confirmed that CC1G_04210 (cpf1) encodes a siderophore synthetase and this NPRS cluster is responsible for the production of coprinoferrin, which is necessary for extracellular iron acquisition and is crucial for the growth and maturation of C. cinerea [46]. Homologous comparison and transcriptome analysis revealed that the NRPS cluster (cluster 6 in Figure S9) in S. rugosoannulata might be responsible for the production of coprinoferrin-related compounds.…”
Section: Discussionmentioning
confidence: 91%
“…Homologous comparison and transcriptome analysis revealed that the NRPS cluster (cluster 6 in Figure S9) in S. rugosoannulata might be responsible for the production of coprinoferrin-related compounds. These NPRS siderophore synthetases are widespread in mushrooms and evolved from a common ancestor of basidiomycetes [46]. Moreover, two other siderophore clusters (clusters 4 and 7 in Figure S9) were predicted by Antismash in the genome of S. rugosoannulata.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The growing interest in fungal SMs is to discover new drugs and to take control of their production. Therefore, novel solutions of activating/regulating "cryptic" BGCs must be developed [13,14]. Hence, an important goal in mining fungal SMs is to characterize the molecular mechanisms of their production [15].…”
Section: Introductionmentioning
confidence: 99%